Taking the Wrong Aim: Policy and Strategy Issues in the Management of Contemporary Security Challenges in Nigeria - Duyile, Praise Fisayo; Aigbe, Endurance Nogiomwan (Kashere Journal of Politics and International Relations, 2025)
Nigeria has become a theater of violent insecurity in the past decades. The country is faced with a multiplicity of security threats that have threatened her existence and rendered the state’s monopoly of the instrument of violence moribund. In an attempt to tackle the menace of insecurity, the Nigerian government formulated the National Counter-Terrorism Strategy (NACTEST) as well as the establishment of the Lake Chad Basin Multinational Joint Task Force (MNJTF). These militaristic initiatives were directed at combating the Boko Haram terrorism that wreaked havoc in major parts of the North-East as of then. However, this extremely state-centric approach has not yielded the needed results owing to the fact that they failed to take cognizance of other security threats that do not subscribe to military strategy. It is against this background that this paper examined an alternative approach to military bombardment as a means to reduce insecurity to its lowest ebb in Nigeria. Relying on secondary data analysis, the paper argued that the prevalent lack of coherence between policy objectives and the actual security strategies implemented often leads to ineffective responses (state-centric approach) to complex threats such as terrorism, insurgency, and other organized crime. The paper therefore recommends adopting a human-centric approach to security, strengthening social protection programs, promoting inclusive governance and participation, promoting economic empowerment and livelihood opportunities, as well as fostering national reconciliation and social cohesion initiatives in order to effectively combat multiple threats and guarantee national security.